Acute and subacute toxicity evaluation of ZhenzhuXiaoji decoction in preclinical models: implications for safe clinical use - Li, Songzhe; Bao, Shuchang; Cai, Lingyun; Li, Baolong; Sun, Yue; Sun, Yang (Frontiers in Pharmacology, 2025)
BackgroundZhenzhuXiaoji Decoction (ZZXJD) is a traditional Chinese medicine formulation composed of five herbs: Ligustrum lucidum, Curcuma zedoaria, Prunella vulgaris, Hedyotis diffusa, and Glycyrrhiza uralensis, developed for the treatment of hepatocellular carcinoma (HCC). Although early studies have demonstrated the therapeutic potential of ZZXJD, its safety profile, particularly regarding potential toxicity, remains underexplored. This study aims to evaluate both the pharmacological effects and toxicity of ZZXJD in preclinical models to determine its clinical applicability.Study design and MethodsThis study employed in vitro and in vivo experiments to assess the pharmacological effects and safety of ZZXJD. HHL-5 and HEK-293 cell lines were treated with ZZXJD at varying concentrations (125, 250, 500, and 1,000 μg/mL) for 24, 48, and 72 h to evaluate its effects on cell viability, apoptosis, and necrosis. Acute and subacute toxicity studies were conducted in male and female mice, including assessments of behavioral changes, body weight, organ weight, and liver/kidney functions. Additionally, routine blood tests were performed to identify potential immunostimulatory effects.ResultsIn vitro experiments demonstrated that ZZXJD inhibited the proliferation of HHL-5 and HEK-293 cells in a dose-dependent manner and induced apoptosis and necrosis. In subacute toxicity studies, mice in the low and mid-dose groups exhibited no significant behavioral changes, whereas the high-dose group showed transient alterations in liver and kidney function markers, particularly in female mice. These changes were reversible following treatment cessation. Blood tests indicated increased lymphocyte and monocyte counts in treated male mice; however, these increases were not statistically significant. Organ weight and histopathological analyses revealed no significant signs of toxicity at therapeutic doses.ConclusionTreatment with ZZXJD at standard therapeutic dosage did not produce acute or subacute toxic effects on liver or kidney functions in vivo, suggesting its safety for continued use in cancer treatment. However, reversible abnormalities in liver and kidney function markers were observed at higher doses. Thus, regular monitoring of liver and kidney functions is recommended during clinical use, especially when higher doses are employed.